Pengaruh Penerapan Gaya Mengajar Komando Terhadap Kemampuan Gerak Dasar Menendang Bola Menggunakan Kaki Bagian Dalam Pada Permainan Sepak Bola Siswa SMP Negeri 5 Tondano - Aditya Bulow; Beatrix J. Podung; A. R. J. Sengkey (STIKES Columbia Asia Medan, 2025)
This study aims to investigate the effect of command teaching style on the ability to kick a ball using the inside of the foot in junior high school students. The research method used is a quasi-experimental design with one group pretest-posttest. The sample consisted of 30 eighth-grade students from SMP Negeri 5 Tondano selected through purposive sampling. Data were collected using pretest and posttest instruments and analyzed using descriptive statistics and paired sample t-test. The results showed a significant increase in posttest scores compared to pretest scores, indicating the effectiveness of the command teaching style in improving the technical ability of kicking a ball with the inside foot. The findings support the application of structured and directive teaching approaches in physical education, particularly in learning fundamental motor skills. This study highlights the relevance of teacher-centered methods for skill acquisition and offers practical implications for physical education practitioners.